KAJIAN PENGARUH KADAR GULA DAN LAMA FERMENTASI TERHADAP KUALITAS NATA de SOYA - Siti Nurhayati (LPPM Universitas Terbuka, 2006)
The aim of the research was to determine the effect of sugar content, time length of fermentations and their interaction on the qualities of the Nata de Soya. The design of the experiment was factorial 3x2 and arranged by the Randomized Complete Design (RCD), with three replications. The first factor was sugar content. G1= 100 g sucrose/l waste of soya, G2= 150 g/l and G3= 200 g/l. The second factor was days of the fermentation F1= 7 days, F2= 14 days. The result showed that (i) the adding of sugar content was not affected the weight, temperature, acidity, moisture content, fiber content and protein content of the Nata de Soya. (ii) The days of fermentation were significant in affecting the weight of the Nata de Soya, but not significant for other parameters. The maximum weight (418,411g) was reached at 7 days of the fermentations. (iii) The interaction between sugar content and time length of fermentations influenced acidity.